Effect of The Addition of Lime (Citrus aurantifolia) on Total Phenolic and Antioxidant of Turmeric Infusion (Curcuma domestica Val.) - Rukmana, Dewi Samudra Putri Aliffa; Rumiati, Flora; Sudrajat, Susana Elya (Jurnal MedScientiae, 2024)
Turmeric is a traditional drink that has been known since ancient times in Indonesia. Turmeric is an herbal ingredient that is efficacious as an antioxidant and is usually combined with tamarind. The added tamarind serves to add to the efficacy of turmeric. In this study, the role of tamarind from sour turmeric drink was replaced with lime fruit. The purpose of this study was to determine the effect of lime powder on pH, antioxidant activity and total phenol of turmeric infusion. Lime turmeric infusion is made by adding water at 900C for 15 minutes. The lime turmeric infusion solution was then tested for pH, total phenol, and antioxidant levels using the DPPH method. Turmeric infusion without the addition of lime fruit powder has a pH of 4.8, total phenol content of 1.324 ± 0.013 mgGAE/g, and antioxidant of 312.55 ± 0.62 ppm. While the turmeric infusion with the addition of lime has a pH of 3.4, a total phenol content of 1.852 ± 0.004 mgGAE/g, and an antioxidant value of 31.80 ± 1.22 ppm. The addition of lime fruit to turmeric infusion resulted in a decrease in pH, an increase in total phenol levels, and antioxidant levels.